Atypical Presentation of Herpes Zoster Infection Following Fludarabine Treatment for Chronic Lymphocytic Leukemia: A Case Report (Annals of Medical Research, 2021)
None
Keywords: Herpes Zoster; Zona; Infection; Fludarabine; Chronic Lymphocytic Leukemia.